Status of selected ion flow tube MS: accomplishments and challenges in breath analysis and other areas - Smith, David; Španěl, Patrik (Bioanalysis, 2016)
This article reflects our observations of recent accomplishments made using selected ion flow tube MS (SIFT-MS). Only brief descriptions are given of SIFT-MS as an analytical method and of the recent extensions to the underpinning analytical ion chemistry required to realize more robust analyses. The challenge of breath analysis is given special attention because, when achieved, it renders analysis of other air media relatively straightforward. Brief overviews are given of recent SIFT-MS breath analyses by leading research groups, noting the desirability of detection and quantification of single volatile biomarkers rather than reliance on statistical analyses, if breath analysis is to be accepted into clinical practice. A 'strengths, weaknesses, opportunities and threats' analysis of SIFT-MS is made, which should help to increase its utility for trace gas analysis.
Keywords: Feces; design vybavení; Equipment Design; Acetonitriles; lidé; feces; Malondialdehyde; Biomarkers; Mass Spectrometry; kolorektální nádory; dechové testy; idiopatické střevní záněty; hmotnostní spektrometrie; Breath Tests; malondialdehyd; těkavé organické sloučeniny; Humans; Colorectal Neoplasms; Inflammatory Bowel Diseases; Volatile Organic Compounds; biologické markery; acetonitrily